2021
DOI: 10.1021/acs.jpcb.0c10681
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement Raises the Energy Barrier to Hydrogen Atom Exchange between Water and Glucose

Abstract: In bulk aqueous environments, the exchange of protons between labile hydroxyl groups typically occurs easily and quickly. Nanoconfinement can dramatically change this normally facile process. Through exchange spectroscopy (EXSY) NMR measurements, we observe that nanoconfinement of glucose and water within AOT (sodium bis(2-ethylhexyl) sulfosuccinate) reverse micelles raises the energy barrier to labile hydrogen exchange, which suggests a disruption of the hydrogen bond network. Near room temperature, we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Graeve and co-workers related changes in reverse micelle size with both cation concentration and hydrated anion radius . If ions reside at the water–surfactant interface as simulations predict and the preponderance of reverse micelle images presented in the literature , , ,,,,, and our cartoon in Figure show, then this would result in an ionic strength gradient that is high at the surfactant interface and lower in the reverse micelle interior.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Graeve and co-workers related changes in reverse micelle size with both cation concentration and hydrated anion radius . If ions reside at the water–surfactant interface as simulations predict and the preponderance of reverse micelle images presented in the literature , , ,,,,, and our cartoon in Figure show, then this would result in an ionic strength gradient that is high at the surfactant interface and lower in the reverse micelle interior.…”
Section: Discussionmentioning
confidence: 91%
“…The vast array of individual environments that the molecules sense along with fast chemical exchange between water molecules means that we only observe the average rather than molecules in any specific environment. 6,8,53 In related studies, the presence of ions added to the reverse micelle interior has been shown to contract the reverse micelle size. 48,49 Graeve and co-workers have observed a reduction in the size of AOT reverse micelles upon addition of ionic compounds such as NH 4 OH, Al(NO 3 ) 3 , ZrOCl 2 .…”
Section: ■ Discussionmentioning
confidence: 98%
“…In previous experiments, we have measured the exchange between water and hydroxyl groups on sugars and sugar alcohols, noting a significant slowing down of the exchange when these molecules are encapsulated in reverse micelles. 40,42,43 We also found evidence for two different regimes wherein the exchange between water and glucose follows expected Arrhenius behavior at higher temperatures but appears to tunnel at a modestly low temperature of around 273 K. 43 Here we explore the chemical exchange between water and urea in bulk aqueous solution and in AOT reverse micelles. The water− urea chemical exchange rate has been reported for bulk aqueous solutions.…”
Section: ■ Introductionmentioning
confidence: 91%
“…These particles have been extensively studied and used because AOT creates remarkably robust aggregates with sizes closely related to the water:AOT ratio . A plethora of studies, from characterizing molecular behavior in nanoconfinement to templating nanoparticle synthesis make AOT reverse micelles exceptionally well characterized. Despite extensive use in research, there is continued debate on the shape of AOT reverse micelles.…”
Section: Introductionmentioning
confidence: 99%